Determinação eletroanalítica do pesticida bendiocarbe - Barbosa, Erineudo Moreira (2018)
The objective of this work was to develop an electroanalytical methodology for the quantification of Bendiocarb (BND) by square wave voltammetry (VOQ) using carbon glass electrode modified with dispersion of carbon nanotubes of multiple walls functionalized in Nafion® / DMF. Analytical curves were obtained by the standard addition method, with the values of LD and LQ being calculated by the standard deviation of ten whites. The buffer solution and pH value optimized for this work were Sörensen 0.1 mol L–1 and pH 7.0. Accumulation potential and times values optimized were 0.60 V and 5 s, respectively. The VOQ parameters were f = 70 s–1, a = 40 mV and ΔEs = 2 mV. The linear range of the analytical curve was 2.99 × 10–6 to 2.06 × 10–5 mol L–1 and linear correlation coefficient (R2) of 0.99 with repeatability 3.78% (n = 7) and reproducibility 2.96% (n = 5). The calculated values for LD and LQ were 1.07 × 10–6 mol L–1 (239 ppb) and 3.58 × 10–6 mol L–1 (799 ppb), respectively. The recoveries in natural waters presented the mean values and relative standard deviation (RPD) of 106.55% ± 2.46%; 84.04% ± 2.33% and 79.34% ± 1.30% for the concentrations 2.99 × 10–6 mol L–1, 1.18 × 10–5 mol L–1 and 2.06 × 10–5 mol L–1, respectively. The method was compared with HPLC, standard method of BND analysis, which presented LD and LQ 1.95 × 10–6 (436 ppb) and 6.52 × 10–6 mol L–1 (1435 ppb), respectively.